2013
DOI: 10.1002/ange.201301875
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonische Synthese von metallischen Nanostrukturen

Abstract: Edelmetall‐Nanostrukturen können in gewünschter Zusammensetzung, Größe und Form und mit ebenso maßgeschneiderten Eigenschaften hergestellt werden. Ihre Anwendungsmöglichkeiten sind äußerst vielfältig und reichen von der Medizin bis zur Elektronik. Besonders interessant ist die Möglichkeit, für ihre Synthese Licht zu verwenden. Im Prinzip kann man mit einer Anregungswellenlänge, die von den Nanostrukturen absorbiert wird, das Wachstum der Partikel gezielt steuern und z. B. aus einer heterogenen Ausgangspopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 212 publications
(507 reference statements)
0
4
0
Order By: Relevance
“…Solution‐based methods, including citrate reduction, the silver mirror reaction, the polyol process, seed‐mediated growth, and plasmon‐mediated synthesis, can often provide easier processes to synthesize AgNPs with shape‐controlled structures . Compared with other methods, plasmon‐mediated synthesis provides a relatively effective approach to study the mechanism of particle formation because these reactions can be terminated immediately by removing the light source. Mirkin et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solution‐based methods, including citrate reduction, the silver mirror reaction, the polyol process, seed‐mediated growth, and plasmon‐mediated synthesis, can often provide easier processes to synthesize AgNPs with shape‐controlled structures . Compared with other methods, plasmon‐mediated synthesis provides a relatively effective approach to study the mechanism of particle formation because these reactions can be terminated immediately by removing the light source. Mirkin et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that different reduction agents will strongly affect the shape distributions and product yields of AgNPs by using direct chemical reduction methods . However, not many photoreduction reagents other than sodium citrate have been used or studied in the literature . When the wavelength of an excitation light source is shorter, it is very probable that more photoreduction reagents can be chosen in photochemical or plasmon‐mediated reactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the scope of this photochemical strategy was still limited to the synthesis of silver nanoparticles for a long time. A large number of studies have shown that the SPR of the seeds of nanoparticles must be excited to induce irreversible photooxidation of adsorbed sodium citrate, thereby promoting the reduction of silver precursor [69–71] . These photochemical reactions may be driven by high‐energy or hot electron‐hole pairs generated by landau damping during photoexcitation of plasmons on the surface of metal nanoparticles [71,72] .…”
Section: Synthetic Methodologymentioning
confidence: 99%
“…A large number of studies have shown that the SPR of the seeds of nanoparticles must be excited to induce irreversible photooxidation of adsorbed sodium citrate, thereby promoting the reduction of silver precursor [69–71] . These photochemical reactions may be driven by high‐energy or hot electron‐hole pairs generated by landau damping during photoexcitation of plasmons on the surface of metal nanoparticles [71,72] . The reduction potential of commonly used gold precursors is lower than that of silver precursors (AuCl 4 − /Au: 0.99 V vs .…”
Section: Synthetic Methodologymentioning
confidence: 99%